Correction: Detection of obstructive sleep apnea using Belun Sleep Platform wearable with neural network-based algorithm and its combined use with STOP-Bang questionnaire - Yeh, Eric; Wong, Eileen; Tsai, Chih-Wei; Gu, Wenbo; Chen, Pai-Lien; Leung, Lydia; Wu, I-Chen; Strohl, Kingman P.; Folz, Rodney J.; Yar, Wail; Chiang, Ambrose A. (PloS one, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0258040.].